Evaluation of diamide insecticides co‐applied with other agrochemicals at various times to manage Ostrinia nubilalis in processing snap bean. Issue 12 (30th January 2015) - Huseth, Anders S; Groves, Russell L; Chapman, Scott A; Nault, Brian A
Abstract BACKGROUND Multiple applications of pyrethroid insecticides are used to manage European corn borer, Ostrinia nubilalis Hübner, in snap bean, but new diamide insecticides may reduce application frequency. In a 2 year small‐plot study, O. nubilalis control was evaluated by applying cyantraniliprole (diamide) and bifenthrin (pyrethroid) insecticides at one of three phenological stages (bud, bloom and pod formation) of snap bean development. Co‐application of these insecticides with either herbicides or fungicides was also examined as a way to reduce the total number of sprays during a season. RESULTS Cyantraniliprole applications timed either during bloom or during pod formation controlled O. nubilalis better than similar timings of bifenthrin. Co‐applications of insecticides with fungicides controlled O. nubilalis as well as insecticide applications alone. Insecticides applied either alone or with herbicides during bud stage did not control this pest. CONCLUSION Diamides are an alternative to pyrethroids for the management of O. nubilalis in snap bean. Adoption of diamides by snap bean growers could improve the efficiency of production by reducing the number of sprays required each season. © 2015 Society of Chemical Industry